1980
DOI: 10.1161/01.cir.62.4.712
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of patients with normal or slightly or moderately abnormal coronary arteriograms: 10-year follow-up of 521 patients.

Abstract: SUMMARY The clinical course was followed for 10 years in 521 patients whose coronary arteriograms did not show any severe obstruction. Coronary disease had been suspected in all patients before arteriography. Two of 357 patients thought to have normal arteriograms died from coronary disease and two of 101 patients died who had less than 30% estimated narrowing of at least one coronary artery. Ten deaths ascribed to coronary disease occurred in 63 patients who had 30-50% narrowing of at least one major coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
0
8

Year Published

1991
1991
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(71 citation statements)
references
References 10 publications
6
57
0
8
Order By: Relevance
“…Survival rate was significantly lower for the subset of patients who suffered from moderate disease. A change in the slope of cardiac survival for this population appears at 5 years; interestingly, this finding is somewhat similar to that reported in a previous study [3]. The kinetics of progression of coronary lesions is one likely explanation.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Survival rate was significantly lower for the subset of patients who suffered from moderate disease. A change in the slope of cardiac survival for this population appears at 5 years; interestingly, this finding is somewhat similar to that reported in a previous study [3]. The kinetics of progression of coronary lesions is one likely explanation.…”
Section: Discussionsupporting
confidence: 90%
“…Patients with moderate disease, defined as 30–50% narrowing in at least one coronary artery, had 10% mortality at 5 years and 25% at 10 years [3, 14, 15]. Similar results were observed in the CASS registry study, the 7- year cardiovascular death rate was 4% for the patients with normal arteriogram and 8% for those whose study revealed mild disease (p < 0.001) [13].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…It is also useful to evaluate the prognosis of the disease, especially in cases with abnormal scintigrams. Factors indicating poor prognosis include the presence of large reversible defects, left ventricular dilatation and an increase in pulmonary uptake' 11 .…”
Section: Introductionmentioning
confidence: 99%